Serum and Glucocorticoid-Inducible Kinase 3/Nedd4-2 Signaling Pathway Participates in Podocyte Injury by Regulating the Stability of Nephrin - Dong, Qing-Qing; Li, Zi-Fang; Zhang, Hui; Shu, Hua-Pan; Tu, Yu-Chi; Liao, Qian-Qian; Yao, Li-Jun (Frontiers in Physiology, 2022)
Serum and glucocorticoid-inducible kinase 3 (SGK3) is involved in maintaining podocyte function by regulating the protein levels of podocin and CD2-associated protein. Nephrin is also one of the slit diaphragm proteins of podocytes, but whether SGK3 participates in podocyte injury by regulating the levels of nephrin remains unclear. In this study, we focused on whether SGK3 affects nephrin levels and the mechanisms involved in the same. In the kidneys of adriamycin (ADR)-induced podocyte injury mouse model, the protein levels of SGK3 and nephrin were significantly decreased. Furthermore, the expression of SGK3 was negatively correlated with the output of proteinuria, and positively correlated with the levels of nephrin. In ADR-treated conditionally immortalized mouse podocyte cells (MPCs), the protein levels of nephrin and SGK3 were inhibited, while the constitutive expression of SGK3 reversed the ADR-induced decline in nephrin protein levels. Furthermore, ADR treatment or SGK3 inactivation enhanced the ubiquitin-proteasome degradation of nephrin in MPCs, and dramatically activated downstream effector proteins of SGK3, neural precursor cells expressing developmentally downregulated protein 4 subtype 2 (Nedd4-2) and glycogen synthase kinase-3 β (GSK3β). Similarly, Nedd4-2 or GSK3β overexpression resluted in increase activity of Nedd4-2 or GSK3β, and significantly downregulated nephrin levels. Interestingly, ubiquitin-mediated protein degradation of nephrin was regulated by Nedd4-2, rather than by GSK3β. In summary, SGK3 inactivation downregulated the levels of nephrin by increasing Nedd4-2 and GSK3β activity in ADR-induced podocyte injury model; in particular, the SGK3/Nedd4-2 signaling pathway was found to be involved in ubiquitin-mediated proteasome degradation of nephrin.